Metabolismo cerebral e permeabilidade da barreira hematoencefálica em um modelo experimental de síndrome da encefalopatia reversível posterior - Marrone, Luiz Carlos Porcello (2016)
Introduction: The Posterior Reversible Encephalopathy Syndrome (PRES) is a clinicoradiologic entity characterized by headache, altered level of consciousness, seizures and visual abnormalities, which is associated with an encephalic white matter edema, predominantly affecting the occipital and parietal lobes. The pathophysiology of PRES remains unclear. In a previous study, we developed an experimental model to better understand the cerebral changes of this syndrome in cases related to pregnancy disorders. The use of microPET-CT with 18F-FDG is a way of assessing brain metabolism changes related to PRES, allowing perform a follow up of these changes in subsequent exams. Objectives: The aim of this study is to evaluate the changes of the glucose cerebral metabolism and the permeability of blood brain barrier in pregnant rats submitted to Reduced Uterine Perfusion Pressure (RUPP) in comparison with pregnant control rats. Methods: Pregnant rats were divided in two groups: RUPP group and control group. Animals of the RUPP group underwent the procedure to reduce uteroplacental perfusion pressure. The animals of both groups were submitted to two microPET-CT scans with 18F-FDG (before and after the delivery) and then, we evaluate the permeability of blood brain barrier using Evans blue. Results: Evaluating the results of microPET-CT scans with 18F-FDG in the ten animals that were submitted to RUPP procedure in comparison with the six pregnant controls animals, there is a cerebral hypometabolism in the exam realized in period before the delivery in the group of rats underwent RUPP. In the postpartum period this result is reversed and the group of animals subjected to the procedure presents a cerebral hypermetabolism when compared to control group. Evaluating the permeability of the blood-brain barrier with Evans blue, 8 of 10 animals (80%) that were submitted to RUPP procedure had the pigment in brain parenchyma, which was not found in any of six animals of the control group. Conclusion: In this study we described a pattern of lower brain metabolism in Wistar rats submitted to RUPP procedure when compared to pregnant control rats before the delivery using microPET-CT with 18F-FDG for this evaluation. After delivery, there is an inversion and the group of animals submitted to RUPP procedure becomes hypermetabolic when compared to the control group using the same technique for measurement of glucose metabolism. The Evans Blue impregnating maintains the same brain tissue after passing seven days of the completion of delivery, and microscopic changes also persist.